2002
DOI: 10.1107/s0907444902013720
|View full text |Cite
|
Sign up to set email alerts
|

Design of specific peptide inhibitors of phospholipase A2: structure of a complex formed between Russell's viper phospholipase A2and a designed peptide Leu-Ala-Ile-Tyr-Ser (LAIYS)

Abstract: Phospholipase A2 (EC 3.1.1.4) is a key enzyme of the cascade mechanism involved in the production of proinflammatory compounds known as eicosanoids. The binding of phospholipase A2 to membrane surfaces and the hydrolysis of phospholipids are thought to involve the formation of a hydrophobic channel into which a single substrate molecule diffuses before cleavage. In order to regulate the production of proinflammatory compounds, a specific peptide inhibitor of PLA2, Leu‐Ala‐Ile‐Tyr‐Ser, has been designed. Phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
0
29
0
3
Order By: Relevance
“…There have also been extensive investigations to understand their (www.interscience.wiley.com) DOI:10.1002/jmr.960 catalytic actions and various ligands have also been designed to inhibit their enzymatic function. The structures of several complexes of PLA 2 with natural compounds (Chandra et al, 2002a(Chandra et al, , 2002dSingh et al, 2006a), substrate analogues (Scott et al, 1990;Thunnissen et al, 1990;Scott et al, 1991;Sekar et al, 1997;Epstein et al, 2001;Pan et al, 2001;Hansford et al, 2003) and with other designed synthetic compounds (Schevitz et al, 1995;Chandra et al, 2002bChandra et al, , 2002cSingh et al, 2003) have also been reported. The anti-inflammatory response of non-steroidal anti-inflammatory drugs (NSAIDs) has been attributed to their binding to PLA 2 (Singh et al, , 2006bJabeen et al, 2005) and COX enzymes Gierse et al, 1999).…”
mentioning
confidence: 98%
“…There have also been extensive investigations to understand their (www.interscience.wiley.com) DOI:10.1002/jmr.960 catalytic actions and various ligands have also been designed to inhibit their enzymatic function. The structures of several complexes of PLA 2 with natural compounds (Chandra et al, 2002a(Chandra et al, , 2002dSingh et al, 2006a), substrate analogues (Scott et al, 1990;Thunnissen et al, 1990;Scott et al, 1991;Sekar et al, 1997;Epstein et al, 2001;Pan et al, 2001;Hansford et al, 2003) and with other designed synthetic compounds (Schevitz et al, 1995;Chandra et al, 2002bChandra et al, , 2002cSingh et al, 2003) have also been reported. The anti-inflammatory response of non-steroidal anti-inflammatory drugs (NSAIDs) has been attributed to their binding to PLA 2 (Singh et al, , 2006bJabeen et al, 2005) and COX enzymes Gierse et al, 1999).…”
mentioning
confidence: 98%
“…The venom PLA 2 does not have calcium ion coordination in the native and complex form. Calcium ion coordination can acquire only when it reacts with aggregated substrates [15,16]. The compounds, which are inhibiting PLA 2 , can be potent anti-inflammatory agents.…”
Section: Inflammationmentioning
confidence: 99%
“…The structures of several complexes of PLA 2 with natural compounds [29][30][31], substrate analogues [17,32], indole derivatives [37][38], non-steroidal anti-inflammatory drugs (NSAIDs) [33][34][35] and with designed peptides [39][40] have been investigated. The substrate-binding site in PLA 2 is a part of the hydrophobic channel.…”
Section: Enzyme-inhibitor Complexesmentioning
confidence: 99%
“…Several structures of PLA 2 complexes with natural compounds [29][30][31], substrate analogues [17,32], nonsteroidal anti-inflammatory drugs (NSAIDs) [33][34][35] and other designed synthetic compounds including peptides [36,[39][40] have been reported. These studies have led to a complete identification of the structural elements of ligand recognition in the hydrophobic channel of PLA 2 , thus paving the way to further improving the quality of inhibitors using structure-based design approach.…”
Section: Introductionmentioning
confidence: 99%